Rapid decrease in total magnetic field F at Antarctic stations - its relationship to core mantle features - Rajaram, G.; Arun, T.; Dhar, Ajay; Patil, A. G. (My University, 2002)
The Indian Institute of Geomagnetism (IIG) in 1982, 1986, and 1996, operated a Proton Precession Magnetometer (PPM) at its Antarctic stations Dakshin Gangotri/Maitri (located at [similar]70°S, [similar]12°E). Comparison of the average quiet-time value of total intensity F for these years with values of F obtained at the same geographic location (interpolated from iso-intensity contours of F on World Magnetic Charts and IGRF Maps) for earlier years, suggested that over the last 75 years at this location, F has dropped from [similar]49 000 nT in 1922, to [similar]40 000 nT in 1996 i.e. [similar]120 nT per year. Further inspection at nearby Antarctic stations reveals a drop of [similar]108 nT yr−1 at Novolazarevskaya, [similar]100 nT yr−1, at Georg Forster and [similar]95 nT yr−1 at Syowa; Mawson situated still further away shows a drop of [similar]72 nT yr−1, while Dumont d'Urville located very near the magnetic pole showed a drop of [similar]50 nT yr−1 until 1994. A study of the observed F values over the past five decades at 23 observatories from the Antarctic and sub-Antarctic regions indicates that contours of yearly decrease in F follow a definite pattern, with maximum decrease lying in a belt encompassing Maitri. These observations are of importance in the light of modelling works at the Earth's Core–Mantle boundary pointing to two prominent regions of reverse magnetic flux (RMF) occurring beneath South America, South Africa and a large part of Antarctica, and which may merge sometime to cause reversal of the present geomagnetic field polarity. The importance of continuous monitoring of F at various locations in Antarctic and sub-Antarctic regions is brought out in this work. It is equally important to understand the cause behind this rapid decrease in F.
Keywords: Core-mantle boundary; Reverse flux regions; Magnetic field; Total magnetic field intensity.; Secular variation; Antarctic stations